Hysteresis of KcsA potassium channel's activation– deactivation gating is caused by structural changes at the channel’s selectivity filter - Tilegenova, Cholpon (Proc Natl Acad Sci U S A, 2017)
Mode-shift or hysteresis has been reported in ion channels. Voltage-shift for gating currents is well documented for voltage-gated cation channels (VGCC), and it is considered a voltage-sensing domain's (VSD) intrinsic property. However, uncoupling the Shaker K(+) channel’s pore domain (PD) from the VSD prevented the mode-shift of the gating currents. Consequently, it was proposed that an open-state stabilization of the PD imposes a mechanical load on the VSD, which causes its mode-shift. Furthermore, the mode-shift displayed by hyperpolarization-gated cation channels is likely caused by structural changes at the channel’s PD similar to those underlying C-type inactivation. To demonstrate that the PD of VGCC undergoes hysteresis, it is imperative to study its gating process in the absence of the VSD. A back-door strategy is to use KcsA (a K(+) channel from the bacteria Streptomyces lividans) as a surrogate because it lacks a VSD and exhibits an activation coupled to C-type inactivation. By directly measuring KcsA’s activation gate opening and closing in conditions that promote or halt C-type inactivation, we have found (i) that KcsA undergoes mode-shift of gating when having K(+) as the permeant ion; (ii) that Cs(+) or Rb(+), known to halt C-inactivation, prevented mode-shift of gating; and (iii) that, in the total absence of C-type inactivation, KcsA’s mode-shift was prevented. Finally, our results demonstrate that an allosteric communication causes KcsA's activation gate to “remember” the conformation of the selectivity filter, and hence KcsA requires a different amount of energy for opening than for closing.